Modelling the Intention and Adoption of Cashless Payment Methods Among the Young Adults in Indonesia - Sutrisna, Ramadhina Putri; Lokeswara, Ken Mithya; Melly, Melly; Rahayu, Fatik (Manajemen & Bisnis Jurnal, 2024)
Cashless payment is gradually replacing physical currency in almost every financial transaction across the world. Even though cashless payment methods have been available in Malaysia since a decade ago, their usage has remained relatively low in comparison to other countries. This study aims to analyse the elements that affect the Malaysian youth’s adoption intention and actual use of cashless payment by extending the unified theory of acceptance and use of technology (UTAUT) model with two key factors (perceived security [PS] and lifestyle compatibility [LC]). The sampling technique used was purposive sampling. Data were analyzed using the Structural Equation Model (SEM) method. The results of this research are: (1) Effort expectancy have a positive effect on intention to use cashless payment, (2) Social influence has a positive effect on intention to use cashless payment, (3) Performance expectancy has a positive effect on intention to use cashless payment, (4) Lifestyle compatibility has a positive effect on intention to use cashless payment, (5) Intention to use cashless payment has a positive effect on adoption of cashless payment. The conclusion of this research is that the antecedents of intention to use cashless payment are effort expectancy, social influence, performance expectancy, and lifestyle compatibility. Meanwhile, the consequence of the intention to use cashless payment is the adoption of cashless payment.